Nonlinear mixed effects height to crown base model for Larix kaempferi plantation in China by considering initial planting density and thinning intensity - Liu, Zhiqi; Liu, Jiateng; Gao, Huilin; Chen, Dongsheng; Lyu, Haiyan (Frontiers in Forests and Global Change, 2025)
Height to crown base is a main component of crown structure to understand the growth of the tree. It is essentially important to construct a comprehensive height to crown base model to facilitate the application in forest management practice decision making. Measurements from a total of 13,822 trees across 159 sample plots developed in the forest stands of Larix kaempferi plantations in Liaoning and Hubei provinces were used to fit the model. Variables of tree size, competition, climate, and thinning practice were considered in the model development. A dummy variable approach was used to analyze the effects of initial planting density and study area on height to crown base, and the interaction between initial planting density and competition was also considered in the height to crown base model. A nonlinear mixed effects model was developed to eliminate heteroscedasticity at the sample plot level. The results showed that the logistic model had the best performance and was therefore selected as the base model. Total tree height and height-diameter ratio from tree level variables, stand basal area of competition variables, spring degree-days below 0°C (DD_0_sp) of climate variables, and thinning variables showed significant contributions to height to crown base and were finally included in the final model. Height to crown base increased with the increase in total tree height, competition, height-diameter ratio, thinning intensity, and decreased with the increase in DD_0_sp and logarithmic transformation of altitude. Large initial planting density resulted in a rise in height to the crown base. The relative contributions of each group of variables to height to crown base were as follows: tree size (41.7%) > competition (27.3%) > thinning (24.5%) > interaction of competition and thinning (3.2%) > climate (2.4%) > site quality (0.9%). The model reveals that thinning mitigates the impact of competition on height to crown base, especially for trees from Hubei province.This comprehensive model provides a robust tool for optimizing Larix kaempferi plantation management strategies and will lay a foundation to conduct forest management strategies decision.